(untitled) (Mustansiria Dental Journal, 2023)
Aims: Oral cavity is attacked by many infectious agents that invade tooth, periodontium and tongue. Dental caries which is the most common oral disease, can caused by the reaction between tooth structure, oral bacteria and fermentable carbohydrates. Most of caries microbial researches considered Streptococcus mutans and lactobacilli as majors caries-associated players. The discovery of Scardovia wiggsiae in 2011 had highlighted the possible occurrence of dental decay in absence of both Streptococcus mutans and lactobacilli in addition to other oral diseases. This review focused on taxonomy, acidogenicity, normal habitat and the important roles of newly S.wiggsiae as the pioneer bacteria for initiation and progression of caries process. Methods: The database was focused on articles published till 2022 for the topics oral diseases, dental caries, Scardovia wiggsiae and microbiology of dental caries Conclusions: Scardovia wiggsiae can to be considered as a potential risk indicator for caries prediction in a given population.